Design of a One-Phase Induction Motor Forward and Reverse Trainer for The Electrical Motor Control Practicum Course - Abdurrahman, Maulana; Lastya, Hari Anna; Ikhsan, Muhammad (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
The Electrical Motor Control course is a crucial in learning about electric drive systems. However, the lack of representative often becomes an obstacle in the learning process. One phase forward reverse motor demonstration tool has never been present in the Electric Motor Control Practical. This study aims to design a forward and reverse single-phase induction motor trainer to be used as a learning medium in the Electrical Motor Control practicum. The research adopts a research and development (R&D) method using the Borg and Gall model, which includes the stages of problem identification, literature review, planning, product design, expert validation, and product revision. The validation instruments used in this study involved media experts and subject matter experts, with two experts in each field evaluating the feasibility of the forward and reverse single-phase induction motor trainer design. Based on the validation results, the material experts gave a score of 94% and the media experts gave a score of 86%, both of which fall into the "highly feasible" category for use in the Electrical Motor Control practicum course. It can be concluded that the developed single-phase forward-reverse induction motor trainer is suitable for use as a learning medium and has the potential to increase the effectiveness of Electric Motor Control practicums.